MANAJEMEN TRANSPORTASI DALAM PENGURAIAN KEMACETAN LALU LINTAS DI KOTA KENDARI - Husen, Osu Oheoputra; Tamburaka, Erny (EDUTECH CONSULTANT, 2019)
The problems studied in the study are how; a) distribution of location of road segments that experience delays (congestion) in Kendari City; b) the level of decomposition of traffic congestion in Kendari City towards the construction of Kendari ring road; and c) transportation management policies in breaking down traffic congestion in Kendari City. This study uses a qualitative approach with the design of surveys and field observations to obtain vehicle volumes and an overview of Kendari City traffic. The data analysis method used is qualitatively which includes analysis of daily traffic (LHR) and LHR prediction in the future and road capacity. The results of the study concluded that the regions that had the highest volume of vehicles and experienced vehicle delays were at three points, namely the Jalan Piere Tendean, Jalan Patimura, and Pungkutoko Port-Access Road. The highest vehicle volume density during the day indicates that the densest activity of the Kendari City community during the day (10-14.00). The construction of the ringroad will have an impact on the level of decomposition of traffic congestion in Kendari City, Kendari, by 30.25%. Transportation management policies in breaking down traffic congestion in Kendari City use two approaches, namely: a) legal aspects, through the issuance of Kendari Regional Regulation (Perda) to regulate / limit the use and / or lane of vehicles, especially heavy vehicles (HV) and divert them on ring road or light vehicles (LV) at certain times / hours; and b) technical aspects, with a traffic demand management (TDM) system as a follow-up to the Perda policy.